2016
DOI: 10.1590/0034-7167-2016-0262
|View full text |Cite
|
Sign up to set email alerts
|

Diálise peritoneal: cuidado familiar ao cliente renal crônico em tratamento no domicílio

Abstract: Objective: to propose a family care model for patients with chronic kidney disease in peritoneal dialysis based on evidence indicated by family members. Method: this was a qualitative descriptive study that used the Convergent Care Research method. It was conducted at a state hospital in Rio de Janeiro, including techniques for recording individual interviews and consisted of a group of 19 study participants. Data were analyzed according to the stages proposed by the method, generating a category that used a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
7
Order By: Relevance
“…When this support is not available, treatment ends up being contraindicated. 8,9 Recent studies on PD incident patients in Brazil (BRAZPD) showed a sociodemographic and clinical profile similar to those identified in this analysis, our study had a higher proportion of Caucasian patients (BRAZPD 60%), due to predominant European colonization in the study region. SAH and DM were the most prevalent comorbidities, corroborating with national data, in which 6,198 patients were evaluated; of these, 40% had diabetes mellitus and 90% had hypertension.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…When this support is not available, treatment ends up being contraindicated. 8,9 Recent studies on PD incident patients in Brazil (BRAZPD) showed a sociodemographic and clinical profile similar to those identified in this analysis, our study had a higher proportion of Caucasian patients (BRAZPD 60%), due to predominant European colonization in the study region. SAH and DM were the most prevalent comorbidities, corroborating with national data, in which 6,198 patients were evaluated; of these, 40% had diabetes mellitus and 90% had hypertension.…”
Section: Resultssupporting
confidence: 79%
“…Studies show that family support is a primary factor for the choice and success of home therapy for patients with incapacity for self-care. 7,8 After 30 days, 89% who started on PD remained on the technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preocupação dos membros da família com a capacitação para realizar a DP de forma segura e eficiente no domicilio é organizada definindo o papel de cada membro, identificando aqueles que serão responsáveis pela DP (5) . Quando se trata especificamente de famílias de crianças que realizam DP, as mães mantêm todos seus esforços focados no tratamento de seus filhos com objetivo de mantê-los vivos (10) , já outra pesquisa mostrou que apesar de todas as dificuldades encontradas no início do tratamento foram superadas com auxilio próprio ou com auxílio da equipe de enfermagem, possibilitando um resultado benéfico no tratamento do seu familiar (11) .…”
Section: Discussionunclassified
“…En el tercer nivel se da a conocer el fundamento científico de la enfermería y otras profesiones que permiten los cuidados interprofesionales encaminados a un abordaje integral de la familia (5). Por último, en el cuarto nivel se configura el plan de decisiones y acciones dirigido a brindar cuidado de enfermería en las modalidades de preservación/mantenimiento, adaptación/negociación o reorientación/reestructuración del cuidado cultural (5,(8)(9)(10)(11)13).…”
Section: Cuidado Culturalmente Congruenteunclassified